The characteristics and correlation of saturated pool boiling critical heat flux for downward-facing plain heating surface. (5th February 2020) - Deng, Kuanghan; Wang, Chenglong; Qiu, Suizheng; Su, G.H.; Tian, Wenxi; Wang, Yun; He, Xiaoqiang
Abstract: The in-vessel retention (IVR) strategy is an effective method to keep the safety of reactor core by external reactor vessel cooling (ERVC) when severe accident occurs. One of the most important concerns is the characteristics of the critical heat flux (CHF) on the outside wall of reactor lower head. In this work, several influence factors on saturated pool boiling CHF for downward facing heating surface were studied, including the type of working fluid, orientation angle and wettability of heating surface. Experimental results indicated that CHF increases with increase of orientation angle of heating surface. It also indicated that both Al2 O3 /H2 O and SiO2 /H2 O nanofluids could improve CHF dramatically compared to deionized water (maximum enhancement rate is 55.5%), but the CHF value of two types of nanofluids is similar to each other, which means type of nanoparticles may has just little influence on CHF. Besides, mechanism of nanofluids enhancing CHF were investigated by measuring the frequency of vapor waves on different heating surface (with and without porous layer). Results showed that the frequency of vapor waves decreases with the increase of heating surface wettability. Furthermore, a new CHF predicted correlation which could fit experimental data well and with excellent applicability was proposed based on experimental results.